Seismic Performance Analysis of Endo Indonesia Office Surabaya Building Structures Against Structural Irregularities - Putra, Mohammad Tomita Maha; Murti, Krisna; Widayanto, Erno (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
The structure of the building will be stable if the response of the structure is able to ignore the static and dynamic loads. The behavioral stability of the building structure is also influenced by geometry, configuration of horizontal and vertical elements, rigidity, lateral ability, and daktility of the structure. (Khanal Chaulagain, 2020). When the structure configuration of the building is irregular, there will be eccentricity which means that the center of the mass is incorrectly at the centre of rigidity (Faisal Darsono, 2019). If such conditions are not anticipated, the structure will be tortured until it eventually collapses. (Naveen dkk., 2019). In Surabaya there are office buildings that have irregular structures. This research will model the structure of the building into five variations. Each variation has a reduction in the value of structural irregularity. Next, we will examine the impact of structural irregularities on the reaction of structures of buildings. The results of the analysis showed that the irregularity of the inner angle had a significant impact on the shift of the roof, with the R-square of 0.9025 in the X axis and 0.9872 in the Y axis. Furthermore, based on the value of the soft level rigidity to the earthquake style at each level, R-quares of 0.8433 were found at the X-axis, and 0.825 at the Y-axe. Furthermore, changes in the inner angle of variations 2, 3, 4, and 5 resulted in successive increases in the mass of the structure by 0.18%, 4.09%, 7.86%, and 0.43%. These increases result in an increase in the basic sliding style in both directions. The variation 5 building designed without an inner angle showed an increase of 0.46% in the base sling style in either direction. Movement targets based on ASCE 41-13 NSP are 321.903 mm and 308.497 mm for the X and Y directions, respectively, which are in the Life Safety and Immediate Occupancy categories. While the total maximum drift values based on ATC-40 for the x and y directions are 0.0148 and 0.0150. The performance of the existing building structure is between B to C on the level of damage control (Immediate Occupancy to Life Safety), which means the building has suffered minor non-structural damage and may suffer structural damage but can still be repaired.